BBX31 promotes hypocotyl growth, primary root elongation and UV-B tolerance in Arabidopsis - Yadav, Arpita (Plant Signal Behav, 2019)
Photomorphogenesis is an important developmental process that helps the seedlings adapt to external light conditions. B-Box proteins are a family of transcription factors that regulate photomorphogenic responses. BBX31 negatively regulates photomorphogenesis under visible light. In contrast, it promotes photomorphogenesis under UV-B and enhances tolerance to high doses of UV-B radiation. BBX31 and HY5 independently and oppositely regulate the ability of seedlings to adapt to varying light intensities. BBX31 also regulates primary root elongation under low intensities of white light. GC-MS and HPLC-based metabolite profiling identified differential accumulation of multiple primary and secondary metabolites in 35S:BBX31 that might enhance tolerance to UV-B.